Quality of life and visual function in patients with intermediate uveitis. Issue 9 (19th August 2005) - Murphy, C C; Hughes, E H; Frost, N A; Dick, A D
Abstract : Aims: To assess visual function, vision related quality of life (VR-QOL), and general health related quality of life (HR-QOL) in intermediate uveitis (IU). Methods: VR-QOL and HR-QOL were evaluated in 42 patients with IU using the VCM1 and SF-36 questionnaires, respectively. LogMAR visual acuity (VA), Pelli-Robson contrast sensitivity (CS), Farnsworth-Munsell 100 hue colour vision (CV), and Estermann visual field (VF) were recorded monocularly and binocularly. Results: Median (interquartile range) visual acuity (VA) and CS of 72 affected eyes were 0.1 (0.015–0.3) and 1.55 (1.35–1.65), respectively. 9.5% of patients had a VCM1 score of more than 2.0, indicating "more than a little" concern over vision. Worse eye VA (p = 0.045) and CS (p = 0.042) were predictive of a VCM1 score of more than 2.0 independently of age, sex, uveitis duration, laterality and activity, systemic uveitis therapy, and medical co-morbidity. The physical and mental component summary scores of the SF-36 were significantly worse in those who reported significant impairment of vision on the VCM1 than those who did not. Conclusions: The majority of patients with IU maintain good visual function and quality of life. VR-QOL impairment in IU correlates with vision in the worse eye and is associated with impaired HR-QOL.